Molecular typing of Leptospira spp. in farmed and wild mammals reveals new host-serovar associations in New Zealand. - Wilkinson DA; Edwards M; Shum C; Moinet M; Anderson NE; Benschop J; Nisa S (Taylor and Francis Group, 2024)
AIMS: To apply molecular typing to DNA isolated from historical samples to determine Leptospira spp. infecting farmed and wild mammals in New Zealand. MATERIALS AND METHODS: DNA samples used in this study were extracted from urine, serum or kidney samples (or Leptospira spp. cultures isolated from them) collected between 2007 and 2017 from a range of domestic and wildlife mammalian species as part of different research projects at Massey University. Samples were included in the study if they met one of three criteria: samples that tested positive with a lipL32 PCR for pathogenic Leptospira; samples that tested negative by lipL32 PCR but were recorded as positive to PCR for pathogenic Leptospira in the previous studies; or samples that were PCR-negative in all studies but were from animals with positive agglutination titres against serogroup Tarassovi. DNA samples were typed using PCR that targeted either the glmU or gyrB genetic loci. The resulting amplicons were sequenced and typed relative to reference sequences. RESULTS: We identified several associations between mammalian hosts and Leptospira strains/serovars that had not been previously reported in New Zealand. Leptospira borgpetersenii strain Pacifica was found in farmed red deer (Cervus elaphus) samples, L. borgpetersenii serovars Balcanica and Ballum were found in wild red deer samples, Leptospira interrogans serovar Copenhageni was found in stoats (Mustela erminea) and brushtail possums (Trichosurus vulpecula), and L. borgpetersenii was found in a ferret (Mustela putorius furo). Furthermore, we reconfirmed previously described associations including dairy cattle with L. interrogans serovars Copenhageni and Pomona and L. borgpetersenii serovars Ballum, Hardjo type bovis and strain Pacifica, sheep with L. interrogans serovar Pomona and L. borgpetersenii serovar Hardjo type bovis, brushtail possum with L. borgpetersenii serovar Balcanica, farmed deer with L. borgpetersenii serovar Hardjo type bovis and hedgehogs (Erinaceus europaeus) with L. borgpetersenii serovar Ballum. CONCLUSIONS: This study provides an updated summary of host-Leptospira associations in New Zealand and highlights the importance of molecular typing. Furthermore, strain Pacifica, which was first identified as Tarassovi using serological methods in dairy cattle in 2016, has circulated in animal communities since at least 2007 but remained undetected as serology is unable to distinguish the different genotypes. CLINICAL RELEVANCE: To date, leptospirosis in New Zealand has been diagnosed with serological typing, which is deficient in typing all strains in circulation. Molecular methods are necessary to accurately type strains of Leptospira spp. infecting mammals in New Zealand.
Keywords: Leptospirosis; New Zealand; livestock; molecular typing; wildlife; Humans; Cattle; Animals; Sheep; Serogroup; New Zealand; Deer; Ferrets; Leptospira; Leptospirosis; Animals, Wild; DNA; Molecular Typing; Cattle Diseases; Sheep Diseases